Effect of Three Different Finishing Processes on the Surface Morphology and Fatigue Life of A357.0 Parts Produced by Laser‐Based Powder Bed Fusion. Issue 7 (18th March 2019) - Gatto, Andrea; Bassoli, Elena; Denti, Lucia; Sola, Antonella; Tognoli, Emanuele; Comin, Andrea; Porro, Juan Antonio; Cordovilla, Francisco; Angulo, Ignacio; Ocaña, Jose Luis
Abstract : A357.0 parts are processed by laser‐based powder bed fusion and surface finished via plastic media blasting, ceramic sand blasting, and laser shock processing. The morphological analysis proves that plastic media blasting causes the most effective peak removal, the most efficient decrease in valley depth, and the greatest reduction in surface roughness. All the surface finishing processes enhance the fatigue life, however ceramic sand blasting bring about the greatest increase in the value of σ max for an infinite fatigue life limit of 2 × 10 6 cycles. The experimental results suggest therefore that the infinite fatigue life value is more sensitive to the residual stress state engendered by ceramic sand blasting than to the reduction in surface roughness. Breakthrough cracks start at the interface between crushed or modified surface particles and the underlying macro‐surface. However, at a distance of a few hundred microns from the crack initiation point, the fracture surface morphology become cellular for all the specimens. Abstract : A357.0 parts are processed by laser‐based powder bed fusion and surface finished via plastic media blasting, ceramic sand blasting, and laser shock processing. All the surface finishing processes enhance the fatigue life, however the infinite fatigue life value is more sensitive to the residual stress state engendered by ceramic sand blasting than to the reduction in surface roughness.